ENDORSEMENT TOWARD CELEBRITIESÃâÃâ INSTAGRAM THAT AFFECT MILLENNIAL BEHAVIOUR: ATTRACTIVENESS OF BEAUTY PRODUCT ENDORSEMENT - Diva Maharani (19015051), Kenira
Endorsement in Instagram is at this point in time becoming a new trend. There were many owners of well-known businesses and start-up businesses who decided to spend their money to corporate with celebrities to promote the product on their instagram’s account, which has many followers. A lot of beauty product businesses that have been endorsed by celebrities and influencers by applying it to themselves in order to review the product. However, within the popularity of celebrities and influencers’ endorsement, there are many endorsers who promote various product endorsements at the same time on their ‘snapgram’ (Instagram’s feature). Where it could possibly changes the behaviour of beauty products’ consumer. The objective of this paper is to identify the changes of consumers’ behaviour towards endorsement on instagram from the business’s point of view. Additionally, this paper will also determine the attractiveness of endorsement in present time. Based on frameworks and theories from prior studies, there were many extensive researches that have been analysed the key model of the study, such as credibility, trustworthy, expertise, etc. Within those models, this paper will use those findings as a base to analyse and compare the current research’s findings. The data would be a primary data, where the interview with several owners of beauty product businesses who are using endorsement on instagram is selected. Therefore, the result of analysis showed that Millennial were attracted to the endorsed product when their celebrity gave a good review on it, which means that trustworthiness is the main key. Quality of product, quality of picture, and quality of endorsers were also become necessary to be considered.